PERAN SEKTOR PARIWISATA TERHADAP PENDAPATAN ASLI DAERAH DI KABUPATEN LAMONGAN - Efeni Nuri Fauziyah Fitriyah; Mohammad Faisal Abdullah; Muhammad Sri Wahyudi Suliswanto (Jurnal Ilmu Ekonomi JIE, 2020)
The purpose of this study was to analyze the influence of the Number of Travelers, Number of Tourism Objects and Number of Hotel Visitors to the Local Revenue of the Lamongan Regency. This type of research uses quantitative research, which uses data published by the Lamongan Regency Central Bureau of Statistics. Then analyzed using Multiple Linear regression uji asumsi klasik.The research results in the first regression show that the number of tourists does not significantly influence the original income of the Lamongan Regency. The results of the second regression show that the number of tourism objects has a significant positive influence on the original income of the Lamongan Regency region and for the third regression result indicates that the variable number of hotel visitors also has a positive but not significant effect on the regional income.